Bedfordshire and Hertfordshire Advance Care Planning Educational Model. Issue 1 (1st June 2011) - Russell, S; Fowler, C
Abstract : The model 1 responds to the challenges of implementing guidance on advance care planning using levels of education need, and the EoLC workforce levels. It is collaboration across Beds and Herts End of Life Network: 3 PCTs, 2 Cancer Networks, 8 independent hospices, 5 acute trusts, 3 community trusts. The coordinated approach is to ensure quality and standardisation. Guidance alone is not able to embed the advance care planning process in practice. The model 1 provides templates for facilitators to deliver the variety of education required for different audiences which include patients, carers and the public. The model 1 uses national documentation and resources for professionals and patients. Steps in the model 1 are: identifying the workforce, identifying different levels of education, delivering education, measuring confidence levels, evaluation, and measurement of impact and consideration of sustainability. The model 1 includes, raising public and professional awareness of what ACP is and who it should matter to, delivering the skills to instigate it and the skills for teaching ACP. A blended learning approach includes face to face learning, e-learning using the National e-learning modules and the East of England EoLC care home education project The model 1 is part of implementation guidance, including: communication, information transfer, documentation, process and a competency based learning framework, so that learning is part of a wider learning experience in End of Life Care.